Digital rurality: Producing the countryside in online struggles for rural survival. (April 2017) - Lundgren, Anna Sofia; Johansson, Anna
Abstract: Interest in the rural has increased in Sweden during the last decades and the rural has become increasingly present as an object of politics, not least in social media. While social media have been recognised for their significance for social movements generally, less is written about how to understand rural movements online. The aim of this article is to study how politics of the rural is performed in and through social media. Seven Sweden-based Facebook accounts were studied using discourse theory. Three different discourses were identified – a discourse of mobilising action, a discourse of re-representation and a discourse of frustration. Of these, we specifically highlight how the focus on urban norms and the practice of performative re-representation constituted the digital arenas as spaces where people who identified with rural areas were linked together, had their experiences and opinions acknowledged and their rural identities not only re-constituted, but recognised and valued. We also show how the different discourses in turn produced two opposing notions of rural areas: as dying or as alive. These two notions worked to structure the politics of the rural in different ways. Highlights: The studied digital politics of the rural was dominated by three different discourses. Conflicting standpoints were kept separate by the social media platform. The medium facilitated the construction of collective movements. Performative re-representation was important in knitting rural identities together. Digital politics of the rural produced imagery of rural areas as both dying and alive.